Social anxiety, loneliness, and mobile phone addiction among nursing students: latent profile and moderated mediation analyses - Yingting Jiang; Zhenrong Shen; Yihao Zeng; Shuhan Li; Hongman Li; Ying Xiong; Zengjie Ye (BMC Nursing)
Abstract Background The overutilization of mobile devices by nursing students has been found to adversely affect their physical and cognitive health, potentially impeding the cultivation of a proficient nursing workforce. Previous research has identified social anxiety and loneliness as influential contributors to mobile phone addiction, but the relationship between these three factors has not been extensively examined. The objective of this research was to investigate the role of loneliness in mediating the relationship between social anxiety and mobile phone addiction, as well as the moderating influence of sleep duration on the relationship between social anxiety, loneliness, and mobile phone addiction among nursing students. Methods We enrolled 437 students from the Be Resilient to Nursing Career program (BRNC) between October and December 2023. Surveys were employed to evaluate the levels of social anxiety, loneliness, and mobile phone addiction among nursing students. Three types of analyses were performed: latent profile analysis, mediation analysis, and moderation analysis. Results The following three profiles of social anxiety were identified: low social anxiety (23.8%), middle social anxiety (42.8%), and high social anxiety (33.4%). The significant mediating effect of loneliness in the relationship between social anxiety based on latent profile analysis and mobile phone addiction was observed (SE = 0.709, 95%CI = 1.821, 4.618; SE = 0.561, 95%CI = 1.161, 3.345, respectively). The moderating role of sleep duration between social anxiety, loneliness, and mobile phone addiction was not significant (P > 0.05). Conclusion Heterogeneity exists in social anxiety among nursing students. Loneliness serves as a significant mediating factor between social anxiety and mobile phone addiction. The moderating influence of sleep duration should be validated in future research.